The Impact of Knee Orthoses on Lameness and Weight Distribution in Canine After Rupture of the Cranial Cruciate Ligament - Aljaž Muršec; Monika Pavlović; Tomaž Lampe; Vladimira Erjavec (Animals)
Cranial cruciate ligament rupture is one of the most prevalent orthopedic injuries in veterinary medicine, significantly impacting canine stifle joint stability and biomechanics, and subsequently, the animal’s quality of life. This study investigates the effectiveness of custom-made knee orthoses as a conservative treatment for recent cranial cruciate ligament ruptures in dogs. Two dogs with cranial cruciate ligament injuries were fitted with individualized orthoses, and their rehabilitation progress was monitored over 32 days. This study employed a four-scale method to measure body weight distribution across limbs and utilized owner questionnaires to evaluate lameness, gait, mobility, and physical activity. The results indicated substantial improvements in both dogs when they wore orthoses. Weight-bearing measurements demonstrated increased load on the injured limb by 0.97 kg and 2.23 kg for Dog 1 and Dog 2, respectively. Dog 2 achieved nearly symmetrical weight distribution by the end of the observation period. Shifts in body weight distribution between forelimbs and hindlimbs highlighted improved functionality; for instance, Dog 1 adjusted from 70% forelimb loading on day 1 to 62% on day 32, while Dog 2 improved from 60% to 55%. Similarly, shifts in lateral weight distribution showed notable reductions in asymmetry, especially in Dog 2, where contralateral load decreased from 59% to 52%. Owner-reported outcomes corroborated these findings, showing enhanced lameness scores, gait quality, and overall mobility. These results underline the potential of custom-manufactured orthoses as a valuable non-surgical approach for cranial cruciate ligament rehabilitation, emphasizing the need for further research in veterinary orthotics to optimize treatment strategies.